Studies on the antiglycating potential of zinc oxide nanoparticle and its interaction with BSA. Issue 18 (12th December 2021) - Kumar, Dinesh; Bhatkalkar, Shruti G.; Sachar, Shilpee; Ali, Ahmad
Abstract: Nanoparticles have been proven to be a great tool as bio-sensors, medical therapeutic agents and drug delivery vehicles. In this study, the chemically synthesized zinc oxide nanoparticles (ZnO NPs) have been characterized with UV-spectrophotometer, FTIR, XRD, TEM and DLS. These ZnO NPs were investigated with respect to their binding interaction with serum albumin and the thermodynamic parameters of these interactions at different temperatures. Glycation process was checked in the presence of ZnO NPs by measuring fructosamine and carbonyl content for glycated end products and aggregation by Congo red assay. The intrinsic activities of bovine serum albumin (BSA) like esterase and cysteine reactivity were also evaluated in the presence of ZnO NPs. The results indicate that the ZnO NPs showed static as well as dynamic binding interaction with BSA, reduced the content of glycation products and prevented the glycation induced aggregation and antioxidant properties. Therefore, these findings suggest that ZnO NPs may be used for drug delivery agents and antiglycating as well as an antioxidant agent. Communicated by Ramaswamy H. Sarma